2020
DOI: 10.2741/4804
|View full text |Cite
|
Sign up to set email alerts
|

Homology between TSH-R Tg TPO and Hashimoto rsquo s encephalopathy autoantigens

Abstract: Introduction 3. Materials and methods 4. Results 5. Discussion 6. Conclusion 7. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…We used our standard procedure, as in previous bioinformatics papers [25] , [26] , [27] , [28] , [29] , [30] , [31] . We retrieved the amino acid sequence of the precursors of the three “classical” human thyroid autoantigens, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used our standard procedure, as in previous bioinformatics papers [25] , [26] , [27] , [28] , [29] , [30] , [31] . We retrieved the amino acid sequence of the precursors of the three “classical” human thyroid autoantigens, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins labeled as “incomplete” or “hypothetical” were excluded. We also excluded alpha-enolase, AKRIAI and DDAHI, since they were investigated in our previous paper [25] . The Protein BLAST (Basic Local Alignment Search Tool) software version 2.8.0+ [32] was used to perform the comparison.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a very unusual scenario CAT is associated with encephalopathy and this association, later defined "steroidresponsive encephalopathy associated with autoimmune thyroiditis (SREAT)" (48) has been described for the first time in 1966 (49). A serological distinctive feature of the disease is the contemporary presence of one or more thyroid antibodies (TgAb, TPOAb and TRAb) and antibodies against brainexpressed autoantigens; amongst the latter anti-alpha-enolase antibodies are the most frequent (50). Interestingly a recent study (50) has shown homologies between TSH-R and alpha-enolase; keeping in mind that main thyroid antigens (Tg, TPO and TSHr) are also expressed in the central nervous system and that alphaenolase is expressed also in the thyroid, a pathogenic contribution of TRAb might be speculated.…”
Section: Clinical Uses Of Tshr Ab In Catmentioning
confidence: 99%